Budaya Organisasi yang Mendukung Inklusi : Menciptakan Lingkungan Kerja yang Beragam dan Sehat - Hanafi, Muhammad; Hasibuan, Wildan Ansori; Ardiansyah, Febry; Kindy S, Mhd Al (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses the importance of an organizational culture that supports inclusion in creating a diverse and healthy work environment. The purpose of this study is to explore the concept of inclusive organizational culture and its impact on employee performance and well-being in various organizations. The method used is a literature review, analyzing sources that address the relationship between organizational culture, diversity, and inclusion. The findings indicate that an inclusive organizational culture can enhance job satisfaction, reduce discrimination, and foster better collaboration in the workplace. The article also emphasizes the crucial role of leadership in shaping a culture that supports diversity and inclusion.